PERAN GURU DALAM MEMFASILITASI PEMBELAJARAN BERBASIS PROYEK DIKELAS RENDAH DI SDN TANAH TINGGI 1 - Denisa, Najwa Putri; Makbullah, Shiva; Azarah, Intan; Bintang, Tiara Kusuma; Ahmad, Fika Fauziah; Nuraeni, Yeni (Cahaya Ilmu Bangsa Institute, 2025)
Teacher involvement in the development of project-based learning (PBL) models in lower grades has a significant impact on how interested students are in learning in the classroom. The role of teachers in creating and implementing PjBL as a method to enhance students' educational experiences is discussed in this literature review. Key elements of the learning paradigm are partly determined by the instructor who acts as the primary facilitator in PjBL. According to the literature, one of the most important first steps is for teachers to have the expertise to select projects that are appropriate to the curriculum and students' level of understanding. By incorporating PjBL into the course content, instructors can enhance students' understanding of the subject matter in a more comprehensive way. The importance of the teacher's work is also demonstrated by their capacity to guide students throughout the project-based learning process. The main factors influencing the efficacy of PjBL are found in the literature because of the teacher's function as a mentor and motivator for students to actively participate, collaborate, and solve problems. This study examines different perspectives and conclusions about the role of teachers in adopting PjBL in lower grades. The findings provide insight into how teachers can use this cutting-edge learning paradigm as a primary driver of increasing students' enthusiasm for learning. better understanding of the role that PjBL teachers play. This is intended to provide direction in creating more successful school policies and teacher preparation programs.